Efficacy of Oral Zinc Supplementation in Radiologically Confirmed Pneumonia: Secondary Analysis of a Randomized Controlled Trial. (30th May 2017) - Bagri, Narendra Kumar; Bagri, Neha; Jana, Manisha; Gupta, Arun Kumar; Wadhwa, Nitya; Lodha, Rakesh; Kabra, Sushil Kumar; Chandran, Aruna; Aneja, Satinder; Chaturvedi, Mona K; Sodhi, Jitender; Fitzwater, Sean Patrick; et al.
Abstract: Objective: To evaluate the effect of zinc as an adjuvant therapy in radiologically confirmed pneumonia in children 2–24 months of age. Patients and Methods: We analyzed data of 212 children with pneumonia for whom chest X-ray films were available at enrollment and at least two radiologists agreed on the diagnosis of pneumonia. We compared the time to recovery in the two groups ( n  = 121, zinc group and n  = 91, placebo group) using a Cox proportional hazards regression model. Results: Time to recovery was similar in both groups [median interquartile range: zinc, 84 h (64, 140 h); placebo, 85 h (65, 140 h)]. The absolute risk reduction for treatment failure was 5.2% (95% confidence interval: −4.8, 15.1) with zinc supplementation. Conclusion: There was no significant beneficial effect of zinc on the duration of recovery or risk of treatment failure in children with radiologically confirmed pneumonia.